MEMBENDUNG WACANA TENTANG KEBEBASAN DAN HAK ASASI MANUSIA BAGI PENYIMPANGAN SEKSUALITAS DENGAN HUKUM DAN AGAMA - Dalmeri Dalmeri (Nizham Jurnal Studi Keislaman, 2016)
After the discourse topic of politics, economics, and advanced law, sensual images in the mass media also becomes such a source of national debate in recent period. The problem is increasingly prominent with definitive arguments about the boundaries between pornography and artistic manifestation of the soul. The case appears when the Polices are busy looking for articles for the appointment of this issue as a the legal case, a chief editor who snagged this case would rationalize the cover of 'beautiful' magazine as an embodiment of appreciation to the maker of beauty. Although, the impressed by the feel of greatness in the expression editor in chief is, essentially it was nothing more than a pretext or an absurd religious jargon, put forward by someone with the function of cognition and conscience that experienced the deviation. This current paper aims to explaine the relevance of discourse about sexuality and the Law about adultery that will be reviewed from the perspective of forensic psychology.